Tamarixia citricola Hansson and Guerrieri sp. nov. (Hymenoptera: Eulophidae): a new parasitoid of Diaphorina citri Kuwayamava (Hemiptera: Psyllidae) found during a classical biological control program in Cyprus - Urbaneja, Alberto; Perez-hedo, Meritxell; Seraphides, Nicos A.; Stalo, Giallouridou; Markou, Lia; C. Stavrinides, Menelaos; Kaponas, Chrysos; Ruiz-Rivero, Omar; J.W. Morgan, David; Hansson, Christer; S. Hoddle, Mark; Anthemis, Melifronidou-Pantelidou; et al. (My University, 2025)
Asian citrus psyllid, Diaphorina citri, is a major global pest because it is the primary vector of Candidatus Liberibacter spp., the causal agents of huanglongbing (HLB), a lethal citrus disease. Following the detection of D. citri in Cyprus in 2023, the first record of this pest in the European Union, a classical biological control program targeting this pest was initiated in spring 2024 using the parasitoid Tamarixia radiata imported from California, USA. During field surveys in summer 2024, parasitized D. citri nymphs were found in orchards where no T. radiata releases had been made. These findings suggested the possible presence of native or unintentionally introduced parasitoids, or a rapid spread of T. radiata into new areas. To determine the identity of parasitoids associated with D. citri in Cyprus, an integrative approach was adopted combining field observations, molecular analyses of the COI gene, and morphological analyses. Tamarixia radiata recovered from Cyprus field sites matched reference sequences of parasitoids from California. However, other specimens were genetically and morphologically distinct and represented a new species. The new species is described here as Tamarixia citricola Hansson & Guerrieri sp. nov. Taxonomic diagnoses and characters for separating both Tamarixia species associated with D. citri are provided. Results presented here indicate the coexistence of both T. radiata (introduced) and T. citricola (likely autochthonous) in Cyprus citrus orchards. This finding has important implications for future biological control strategies and quarantine measures for D. citri in the Mediterranean basin.
Keywords: ACP; huanglongbing; classical biological control; integrative taxonomy; psyllid parasitoids; COI barcoding